DOMINATION OF PUBLIC SPHERE AND REPUTATION OF PREACHER IN SOCIAL MEDIA (JOURNAL OF INDONESIAN ISLAM, 2024)
Online social media has been widely used by Muslim preachers in Indonesia. This research critically examines the activities of Instagram account @edhnx which spreads da‘wa messages of popular preachers massively on his Instagram account. The research uses a qualitative approach with virtual ethnographic methods. The context of public space which is close to freedom actually harbors discourses of domination and reputation. The da‘wa messages from popular preachers are deliberately disseminated to get audience responses in the form of opinions, interactions and participation. As it progressed, audience responses became increasingly diverse. This then creates an ideal public space, namely a public space that fulfills the activities of a multicultural society. Thus, social media accounts are not only used as a space for mutually beneficial interaction. Ownership of public space gives rise to control of digital public space through preaching messages that can be carried out by anyone without having to first become a preacher. Social media accounts ultimately become an ideal public space to demonstrate dominance as a subject controlling space which can be done openly and freely by utilizing da‘wa messages.